Physical Education Professionals and their Role in Primary Care in Curitiba - Diego Spinoza; Marcelo Guimarães; Letícia Carneiro; Lucélia Borges (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to describe the inclusion of the Physical Education professor, relating historical aspects and outlining the role of these professionals in Primary Care in Curitiba, Brazil. Inclusion occurred in 2009 with the hiring of 29 professionals, 26 of whom were still employed in early 2016. Activities performed include exercise groups; individual care; clinical support; continuing education; health education; as well as participation in social control, by representing the profession at the Municipal Health Council of Curitiba and Teaching-Service integration via a Multidisciplinary Residency preceptorship. The historical background reveals advances, achievements and much more to accomplish, in a permanent and ongoing process.